PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA RUMAH SAKIT BP. BATAM - Karo-Karo, Sentosa; Tamami, Sastra (BENING, 2016)
This study aims to determine influence the development of human resource and leadership style and employee performance BP. Batam Hospital. In this research, total population 237 people with using help of slovin formula with the fault tolerance 10% get sample of 70 people to serve as respondents. Whereas the type of data used data premier and secondary data. Premier data sources from the questionnaire. While secondary data from BP. Batam Hospital documents and obtained from the literature related and can support as well as useful for this study. Techniques analysis data is do with validity test and reliability test, classical assumption test, doulde linear analysis, hypothesis testing, and coefficient of determination (R2). The test using SPSS (Statistical Product and Service Solution) version 20. From the study authors conclude that the development of human resources (X1) are not positive and significant impact on employee (Y) and leadership style (X2) are positive and significant, whereas the development of human resources (X1) and leadership style (X2) together positive and significant impact on employee performance (Y).Keywords: Development of Human Resource, Leadership Style, Performance